Evaluation of potential exposure risks of natural radioactivity levels emitted from building materials used in Adana, Turkey - Turhan, Şeref; Solak, S.; Uğur, F.A.; Gören, E.; Gezer, F.; Yeğingil, Z.; Yeğingil, İ. (Indoor and Built Environment 2014 23: 594 originally published online 29 May 2012, 2012)
In this paper, the natural radioactivity levels in a total of 117 samples of 14 different building materials collected from building construction sites and from the retailers in Adana were studied by means of gamma-ray spectrometer with HPGe detector. The mean activity concentrations of 226Ra, 232Th and 40K measured in the studied building material samples ranged from 2.1 to 88.2 Bq kg1 , 1.8 to 52.7 Bq kg1 and 68.1 to 847.5 Bq kg1 for 226Ra, 232Th and 40K radionuclide, respectively. The external and internal index, the indoor absorbed dose rate and the corresponding annual effective dose were evaluated for potential exposure risks from the usage of the building material samples. The evaluated values of the external and internal index were below the recommended upper level. All the values of effective annual dose determined were lower than recommended exemption level of 0.3 mSv. The results suggest that the use of the studied building material samples in the construction of buildings is unlikely to give rise to any significant radiation exposure to the residents.
Keywords: Radioactivity, Building material, Gamma-ray spectrometer, External index, Internal index, Annual effective dose